Strategi Marketing Mix Perspektif Ekonomi Islam pada Hotel Semesta di Kota Semarang - Farkhi Hazami; Rosida Dwi Ayuningtyas (Universitas Wahid Hasyim, 2018)
This research is a qualitative research to examine the application of Islamic economic perspective marketing in the business of sharia services in Semarang City, a case study in the sharia industry in the Sharia Universe of Semarang City. The focus of this research is to explain how the application of Islamic economic perspective marketing mix to hotel universe sharia. In this study focuses on product, price, promotion, distribution / place carried out by the hotel universe syariah city all the perspectives of Islamic economics theoretically. The purpose of this study is to provide a conclusion about the application of marketing mix namely product, price, promotion, and distribution / place carried out by hotel universe syariah Islamic economic perspective. This study uses a qualitative approach to the case study method. The data analyzed are the results of interviews, documentation and observations with the field of marketing, namely product, price, promotion, and distribution / place in the Semarang Sharia Universe Hotel. The results showed that the application of Islamic economic perspective marketing mix at the Semarang City Semesta Hotel had not been effective. Because in terms of Sharia Universe Hotel products still have not fully implemented several elements and sub elements provided by the Republic of Indonesia's Creative Economy Tourism Minister Regulation Number 2 of 2014 concerning guidelines for sharia hotel business operators. Keywords: Strategy, Marketing mix, Islamic Perspective, Sharia Industry